2017
DOI: 10.1159/000481465
|View full text |Cite
|
Sign up to set email alerts
|

miR302a-3p May Modulate Renal Epithelial-Mesenchymal Transition in Diabetic Kidney Disease by Targeting ZEB1

Abstract: Background: Recent study found that microRNA (miRNA) are involved in diabetic kidney disease (DKD). The objective of this study is to determine the role of miR302a-3p in the process of renal epithelial-mesenchymal transition (EMT) in DKD. Methods: The miRNA expression profiling of the cell line stimulated by high glucose was performed by a microarray analysis. Then real-time polymerase chain reaction (PCR) were used to determine the expression of one of the miRNAs significantly upregulated in cell line stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…According to the finding that dsEcad640 suppressed the expression of ZEB1 mRNA and upregulated the expression of E‐cadherin through combination with ZEB1 coding sequence, and miR‐302a has the same seed sequence, we used the method of Target Scan bioinformatics prediction to verify the relationship between miR‐302a and ZEB1. The result demonstrated ZEB1 might be a potential target of miR‐302a, and miR‐302a may play a protective role in high glucose‐induced EMT of HK‐2 cells by downregulation the expression of ZEB1, which was in agreement with the previous study (Tang, Zheng, & Yan, ). More remarkable, mulberry leaves are beneficial in treatment of EMT considering its ameliorative effect on the miR‐302a and ZEB1 expression.…”
Section: Discussionsupporting
confidence: 92%
“…According to the finding that dsEcad640 suppressed the expression of ZEB1 mRNA and upregulated the expression of E‐cadherin through combination with ZEB1 coding sequence, and miR‐302a has the same seed sequence, we used the method of Target Scan bioinformatics prediction to verify the relationship between miR‐302a and ZEB1. The result demonstrated ZEB1 might be a potential target of miR‐302a, and miR‐302a may play a protective role in high glucose‐induced EMT of HK‐2 cells by downregulation the expression of ZEB1, which was in agreement with the previous study (Tang, Zheng, & Yan, ). More remarkable, mulberry leaves are beneficial in treatment of EMT considering its ameliorative effect on the miR‐302a and ZEB1 expression.…”
Section: Discussionsupporting
confidence: 92%
“…102 In addition, miR-302a-3p exerted a protective role via inhibiting ZEB1 and EMT in diabetic kidney disease. 103 These results suggest that…”
Section: Zeb Transcription Factorsmentioning
confidence: 81%
“…Moreover, the heterogeneous expression of ZEB1 induced by EMT played an important role in metastasis through the regulation of miR‐200c . In addition, miR‐302a‐3p exerted a protective role via inhibiting ZEB1 and EMT in diabetic kidney disease . These results suggest that various mediators contribute to EMT via the ZEB signaling pathway, suggesting that ZEB is a promising target for the treatment of fibrosis and tumors.…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…miRNAs negatively regulate the expression of their target genes by inducing the degradation of messenger RNAs (mRNAs) and/or inhibiting the translation of the proteins from the mRNAs (4). Increasing evidence has indicated that the dysregulation of miRNAs may be involved in the pathogenesis and development of DKD (5,6). Previous studies have also revealed that miR-342-3p is highly expressed in mouse kidney tissues; however, whether miR-342-3p is associated with the progression of DKD remains unknown.…”
Section: Introductionmentioning
confidence: 99%